Diagnosis and treatment of MYH9-RD in an Australasian cohort with thrombocytopenia. (17th November 2018) - Rabbolini, David J.; Chun, Yenna; Latimer, Maya; Kunishima, Shinji; Fixter, Kathleen; Valecha, Bhavia; Tan, Peter; Chew, Lee Ping; Kile, Benjamin T.; Burt, Rachel; Radhakrishnan, Kottayam; Bird, Robert; et al.
Abstract: MYH9 -related disorders ( MYH9 -RDs) caused by mutation of the MYH9 gene which encodes non-muscle myosin heavy-chain-IIA (NMMHC-IIA), an important motor protein in hemopoietic cells, are the most commonly encountered cause of inherited macrothrombocytopenia. Despite distinguishing features including an autosomal dominant mode of inheritance, giant platelets on the peripheral blood film accompanied by leucocytes with cytoplasmic inclusion bodies (döhle-like bodies), these disorders remain generally under-recognized and often misdiagnosed as immune thrombocytopenia (ITP). This may result in inappropriate treatment with corticosteroids, immunosupressants and in some cases, splenectomy. We explored the efficacy of next generation sequencing (NGS) with a candidate gene panel to establish the aetiology of thrombocytopenia for individuals who had been referred to our center from hematologists in the Australasian region in whom the cause of thrombocytopenia was suspected to be secondary to an inherited condition but which remained uncharacterized despite phenotypic investigations. Pathogenic MYH9 variants were detected in 15 (15/121, 12.4%) individuals and the pathogenecity of a novel variant of uncertain significance was confirmed in a further two related individuals following immunofluorescence (IF) staining performed in our laboratory. Concerningly, only one (1/17) individual diagnosed with MYH9 -RD had been referred with this as a presumptive diagnosis, in all other cases (16/17, 94.1%), a diagnosis was not suspected by referring clinicians, indicating a lack of awareness or a failing of our diagnostic approach to these conditions. We examined the mean platelet diameter (MPD) measurements as a means to better identify and quantify platelet size. MPDs in cases with MYH9 -RDs were significantly larger than controls ( p < 0.001) and in 91% were greater than a previously suggested threshold for platelets in cases of ITP. In addition, we undertook IF staining in a proportion of cases and confirm that this test and/or NGS are satisfactory diagnostic tests. We propose that fewer cases of MYH9 -RDs would be missed if diagnostic algorithms prioritized IF and/or NGS in cases of thrombocytopenia associated with giant platelets, even if döhle-like bodies are not appreciated on the peripheral blood film. Finally, our report describes the long-term use of a thrombopoietin agonist in a case of MYH9 -RD that had previously been diagnosed as ITP, and demonstrates that treatment with these agents may be possible, and is well tolerated, in this group of patients.